Antibiotics misused miracles? - Bouchardeau, Cecile; Discovery Health Channel ([Sl.L.] : CBS News Productions (production company) ; Singapore : International Publishers Direct [distributor], 2004)
This program shows how we have misused of antibiotics ; use of antibiotics in agriculture and new uses of antibiotics.
Executive producer, Joel Heller
Narrator: Richard Schlosinger
Keywords: Antibiotics